Analisis Faktor Keputusan Mahasiswa Dalam Memilih Belajar di Fakultas Ekonomi Universitas Darma Persada - Deddy Wibowo Adhinugroho (Universitas Serang Raya, 2022)
The Faculty of Economics, Darma Persada University (FE Unsada) is higher education institution’s unit, that aims to prepare skilled professionals educated in the fields of economics, business and accounting, by specifically adding Japanese-style management knowledge as a reference from developed countries in the fields of economy, industry and technology, which is expected to provide special characteristics and added value in learning to attract students' interest, compared to those offered by other similar higher education institutions as competitors. However, in its progress over the last two years (2018-2020), there has been a decrease in the number of students who are interested in studying at FE Unsada. So, through this research, it is expected to be able to find out and measure the dominant factors that are taken into consideration by students choosing to study at FE Unsada, so that further anticipation can be done to decrease the number of students and restore increased interest of students through attractive strategy programs and answer the needs and expectations of students. This research was conducted with a quantitative descriptive method, factor analysis through a series of statistical validity tests and values tests, using a questionnaire technique with a random sample of 126 students of FE Unsada class 2016-2020, where from the results of the study it was found that there were three main factors that formed the choice of students to study at FE Unsada, namely: 1. Campus Reputation (36.49%), 2. Social Environment Influences (12.12%), 3. Socio-economic Status (9.72%). Keywords : Factor analysis; Student intention; Economic Faculty; Consumer Behavior.